2014
DOI: 10.1016/j.antiviral.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental rhinovirus infection in COPD: Implications for antiviral therapies

Abstract: Chronic obstructive pulmonary disease (COPD) is a major public health problem and will be one of the leading global causes of mortality over the coming decades. Much of the morbidity, mortality and health care costs of COPD are attributable to acute exacerbations, the commonest causes of which are respiratory infections. Respiratory viruses are frequently detected in COPD exacerbations but direct proof of a causative relationship has been lacking. We have developed a model of COPD exacerbation using experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 116 publications
1
19
0
Order By: Relevance
“…In addition, the changes in inflammatory profile, less frequent detection in steady state and the seasonal changes in exacerbation rate suggest that viral acquisition is causally related to exacerbation [9][10][11][12]. Furthermore, recent challenge studies with human rhinovirus in patients with COPD have replicated the symptoms and inflammatory profile changes associated with naturally occurring exacerbations [13]. Studies examining bacterial and viral co-infection in COPD exacerbations have suggested a synergistic relationship between the two [12,14], with a recent study demonstrating a quantitative change in bacteria in the lower respiratory tract of COPD patients following experimental rhinovirus challenge [15].…”
Section: Introductionmentioning
confidence: 68%
“…In addition, the changes in inflammatory profile, less frequent detection in steady state and the seasonal changes in exacerbation rate suggest that viral acquisition is causally related to exacerbation [9][10][11][12]. Furthermore, recent challenge studies with human rhinovirus in patients with COPD have replicated the symptoms and inflammatory profile changes associated with naturally occurring exacerbations [13]. Studies examining bacterial and viral co-infection in COPD exacerbations have suggested a synergistic relationship between the two [12,14], with a recent study demonstrating a quantitative change in bacteria in the lower respiratory tract of COPD patients following experimental rhinovirus challenge [15].…”
Section: Introductionmentioning
confidence: 68%
“…It is estimated that viral or bacterial infections or combination of both are responsible from two thirds to three quarters of all COPD exacerbations [11,34]. The role of respiratory viruses as pathogens provoking the majority is increasingly recognized [35][36][37]. Owing to clinical availability of multiplex PCR, detection of respiratory viruses has been greatly facilitated in the recent years.…”
Section: Acute Exacerbation Of Copdmentioning
confidence: 99%
“…Several drug candidates have been progressed into clinical trials, including a viral 3C protease inhibitor, and different compounds that prevent virus attachment and entry into cells by binding to the viral capsid (Gunawardana et al, 2014). However, none of these candidates were commercialized due to unacceptable side effects or lack of efficacy when applied to the natural setting [10].…”
Section: Introductionmentioning
confidence: 99%